(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The relationship between anthropometric characteristics and playing ability in Basketball has been a topic of interest in sports science research. Understanding the correlation between these variables can provide valuable insights for talent identification, player development, and training programs. The aim of this study was to investigate the correlation between anthropometric characteristics and playing ability among school-level male Basketball players in Punjab. A total of 250 male Basketball players were selected using purposive sampling from various regions of Punjab. Anthropometric measurements were taken using standardized protocols, including variables such as upper arm length, lower arm length, total arm length, hand length, hand span, upper leg length, lower leg length, total leg length, upper arm circumference, forearm circumference, thigh circumference, calf circumference, biacromial diameter, wrist diameter, biceps skinfold, suprailiac skinfold, subscapular skinfold, and triceps skinfold. The playing ability of the participants was assessed using the AAHPERD Basketball skill test, which measures various aspects of Basketball performance, including shooting, dribbling, passing, and agility.